Child Marriage and Sexual Abuse of a Girl Child after Marriage – A Glimpse With Indian Law: Examining the Real Status of Women in Underage Marriages (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In India child marriages still take place in various regions usually in rural and semi-urban areas. Some states made the child marriage below the age of 18 is a crime and the marriage will be declared null and void and it is also a punishable act. But in some states due to improper vigilance and manifestation of the social norms still persist. And this article is written with the objective to study the sexual abuse of a married woman who is under the age of 18. This article will cover the various state norms and the court ruling which depicts the real status of women getting married and suffering in the relationships are still minor and not yet attained age maturity.